2013
DOI: 10.1242/jcs.129437
|View full text |Cite
|
Sign up to set email alerts
|

Drebrin preserves endothelial integrity by stabilizing nectin at adherens junctions

Abstract: SummaryRegulation of cell-cell contacts is essential for integrity of the vascular endothelium. Here, a critical role of the F-actin-binding protein drebrin in maintaining endothelial integrity is revealed under conditions mimicking vascular flow. Drebrin knockdown leads to weakening of cell-cell contacts, characterized by loss of nectin from adherens junctions and its subsequent lysosomal degradation. Immunoprecipitation, FRAP and mitochondrial re-targeting experiments show that nectin stabilization occurs th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 74 publications
0
22
0
Order By: Relevance
“…Through the PDZ domain, both l‐afadin and s‐afadin bind to the cell adhesion molecule (CAM) nectin, which comprises a family with four members (nectin‐1, nectin‐2, nectin‐3, and nectin‐4) through their cytoplasmic tails (Takai, Ikeda, Ogita, & Rikitake, ; Takai, Miyoshi, Ikeda, & Ogita, ). In addition to nectin, many proteins, including Rap1 small G protein, αE‐catenin, p120 ctn , PLEKHA7, ZO‐1, ponsin, ADIP, LMO7, and drebrin, bind to l‐afadin through its respective binding domains (Asada et al., ; Boettner, Govek, Cross, & Van Aelst, ; Hoshino et al., ; Kurita, Yamada, Rikitsu, Ikeda, & Takai, ; Linnemann et al., ; Mandai, Rikitake, Shimono, & Takai, ; Mandai et al., ; Miyata et al., ; Ooshio et al., , ; Rehm, Panzer, van Vliet, Genot, & Linder, ; Tachibana et al., ; Takahashi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Through the PDZ domain, both l‐afadin and s‐afadin bind to the cell adhesion molecule (CAM) nectin, which comprises a family with four members (nectin‐1, nectin‐2, nectin‐3, and nectin‐4) through their cytoplasmic tails (Takai, Ikeda, Ogita, & Rikitake, ; Takai, Miyoshi, Ikeda, & Ogita, ). In addition to nectin, many proteins, including Rap1 small G protein, αE‐catenin, p120 ctn , PLEKHA7, ZO‐1, ponsin, ADIP, LMO7, and drebrin, bind to l‐afadin through its respective binding domains (Asada et al., ; Boettner, Govek, Cross, & Van Aelst, ; Hoshino et al., ; Kurita, Yamada, Rikitsu, Ikeda, & Takai, ; Linnemann et al., ; Mandai, Rikitake, Shimono, & Takai, ; Mandai et al., ; Miyata et al., ; Ooshio et al., , ; Rehm, Panzer, van Vliet, Genot, & Linder, ; Tachibana et al., ; Takahashi et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…5C). Further mutagenesis analysis with DBN1 mutants (31) revealed that the most N-terminal ADF-H domain within DBN1 is responsible for restriction of viruses and other cargo (SI Appendix, Fig. S10C).…”
Section: Dbn1 Negatively Regulates the Endocytosis Of Dynamin-dependentmentioning
confidence: 99%
“…The drebrin-based protein complex is known to stabilize F-actin, modifies microfilament structure, or moderates the interactions of other actin-binding proteins with actin microfilaments. For instance, drebrin binds to afadin to connect F-actin to nectin-based integral membrane proteins (Rehm et al 2013). It competes with tropomyosin for F-actin binding and inhibits actin-binding and cross-linking activity of α-actinin (Ishikawa et al 1994).…”
Section: 3 Drebrin In the Testismentioning
confidence: 99%
“…Drebrin E, besides expresses similarly to Arp3 spatiotemporally during the epithelial cycle, also has high affinity to bind to Arp3, illustrating that drebrin E may recruit Arp3 to the ES to induce F-actin reorganization and to alter apical ES dynamics to facilitate spermiation. It has been reported that AJ integrity in endothelial cells is stabilized by drebrin since the knockdown of drebrin by RNAi in human umbilical vein endothelial cell (HUVEC), an endothelial cell line, leads to impairment of endothelial cell-cell junctions by causing mis-localization of afadin, thereby impeding the localization of nectin-2 and nectin-3 at the cell-cell interface (Rehm et al 2013). It is of interest to note that treatment of Sertoli cells with a functional TJ barrier in vitro with TNFα and TGFβ3 that downregulates drebrin E expression also increases structural interaction between drebrin E and Arp3 (Li et al 2011), illustrating an increase in the intrinsic branched actin polymerization activity.…”
Section: 4 Drebrin E and Ectoplasmic Specialization (Es) Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation